2021
DOI: 10.3390/biomedicines9091278
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-Dependent and -Independent (Moonlighting) IκBα Functions in Differentiation and Cancer

Abstract: IκBα is considered to play an almost exclusive role as inhibitor of the NF-κB signaling pathway. However, previous results have demonstrated that SUMOylation imposes a distinct subcellular distribution, regulation, NF-κB-binding affinity and function to the IκBα protein. In this review we discuss the main alterations of IκBα found in cancer and whether they are (most likely) associated with NF-κB-dependent or NF-κB-independent (moonlighting) activities of the protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…These data were compared with the results of the FSK treatment. FSK is an adenylate cyclase activator that acts by increasing the Besides, IκBα is a crucial regulator of the transcription factor NF-κB, and deregulation of IκBα cellular levels impacts a variety of diseases, including chronic inflammatory diseases and cancers (34,35). Western blotting results revealed that ketoprofen-RGD increased IκBα protein expression and counteracted the suppressive effects of LPS.…”
Section: Discussionmentioning
confidence: 99%
“…These data were compared with the results of the FSK treatment. FSK is an adenylate cyclase activator that acts by increasing the Besides, IκBα is a crucial regulator of the transcription factor NF-κB, and deregulation of IκBα cellular levels impacts a variety of diseases, including chronic inflammatory diseases and cancers (34,35). Western blotting results revealed that ketoprofen-RGD increased IκBα protein expression and counteracted the suppressive effects of LPS.…”
Section: Discussionmentioning
confidence: 99%
“…The NFKB inhibitor alpha ( NFKBIA ) gene at 14q13.2 encodes the alpha subunit of the inhibitors of κB (IκBα), proteins that regulate the activity of transcription factor nuclear factor κB (NF-κB) in the cytoplasm. 23 Evidence that, in chromatin, nuclear NFKBIA dynamically interacts with histones H2A and H4 to regulate polycomb-dependent transcriptional repression and, thus, stem cell maturation, lineage specification, and cancer 24 , 25 , 26 and our characterization of NFKBIA as a tumor suppressor in glioblastoma 27 prompted our investigation of the relationship of NFKBIA deletions with other genetic markers, alterations in the methylome, and the clinical course of gliomas. We analyzed the genetic profiles of gliomas of multiple well-characterized patient populations to determine whether incorporation of NFKBIA deletions could enhance the prognostic value of current molecular descriptions.…”
Section: Introductionmentioning
confidence: 99%
“…Then, N‐terminal part of p100 that shows NF‐κB2 p52 translocates into the nucleus by binding to RelB (Cildir et al, 2016; Feige et al, 2018). More details about NF‐κB signaling can be found in recent reviews (Figure 1) (Espinosa & Marruecos, 2021; Gilmore, 2021; Silke & O'Reilly, 2021).…”
Section: Introductionmentioning
confidence: 99%